2016
DOI: 10.1681/asn.2016030320
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial to Reduce Disparities in Referral for Transplant Evaluation

Abstract: Georgia has the lowest kidney transplant rates in the United States and substantial racial disparities in transplantation. We determined the effectiveness of a multicomponent intervention to increase referral of patients on dialysis for transplant evaluation in the Reducing Disparities in Access to kidNey Transplantation Community Study (RaDIANT), a randomized, dialysis facility-based, controlled trial involving >9000 patients receiving dialysis from 134 dialysis facilities in Georgia. In December of 2013, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 27 publications
3
108
0
Order By: Relevance
“…Although national transplant referral data are unavailable, we recently collected patient referral data from all Georgia transplant centers as part of the Reducing Disparities in Access to Kidney Transplantation Community Study, and an extension of this data collection in other states is underway (13). The few studies that have examined transplant performance using transplant referral have used facility-level absolute referral rate to measure facility performance (3,14,15). In a recent study, we examined whether absolute facility referral was associated with other quality metrics within dialysis facilities and found that referral was not associated with other metrics, such as anemia management, morbidity, or mortality, and although referral was associated with waitlisting and transplantation, it was not entirely correspondent with these other measures of transplant access.…”
Section: Introductionmentioning
confidence: 99%
“…Although national transplant referral data are unavailable, we recently collected patient referral data from all Georgia transplant centers as part of the Reducing Disparities in Access to Kidney Transplantation Community Study, and an extension of this data collection in other states is underway (13). The few studies that have examined transplant performance using transplant referral have used facility-level absolute referral rate to measure facility performance (3,14,15). In a recent study, we examined whether absolute facility referral was associated with other quality metrics within dialysis facilities and found that referral was not associated with other metrics, such as anemia management, morbidity, or mortality, and although referral was associated with waitlisting and transplantation, it was not entirely correspondent with these other measures of transplant access.…”
Section: Introductionmentioning
confidence: 99%
“…2 Agents targeting the IL-1 system (either IL-1 inhibitors or IL-1 receptor antagonists) have proven to be effective in some systemic inflammatory diseases, such as gout, rheumatoid arthritis, and adult-onset Still disease. Rilonacept is a soluble decoy receptor protein that acts by binding to IL-1a and Il-1b, thereby preventing activation of IL-1 receptors, 3 and has regulatory approval for treatment of a rare group of genetic inflammatory syndromes.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Most patients on dialysis are unable to complete the first three steps, which occur before transplant providers are involved. 2 In this issue of the Journal of the American Society of Nephrology, Patzer et al 3 show that interventions directed at dialysis facility practices can improve transplant referral, a task that reflects successful completion of the first three steps in the kidney transplant process. The authors randomly assigned 134 Georgia facilities to a control group that received usual care or an intervention group that received transplant education and engagement activities that targeted dialysis facility leadership, staff, and patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 10 years, many patient, provider, system, and policy interventions to improve access to transplant have been recommended and tested (5)(6)(7). At a Consensus Conference on Best Practices in Live Kidney Donation, for example, 67 leaders aligned around recommendations to reduce racial disparities that included removing financial disincentives to transplant; implementing culturally tailored, community-based education at multiple stages of the transplant referral process; engaging a transplant liaison; and developing a research strategy to better understand transplant disparities (8).…”
mentioning
confidence: 99%